Does military expenditure influence economic growth in Nigeria during 1989 - 2013? A bound testing approach - Tolulope Olumuyiwa Apanisile; Charles Olalekan Okunlola (Romanian Journal of Fiscal Policy (RJFP), 2014)
The study examines the effect of military expenditure on output in Nigeria both in the short-run and in the long-run period. In addition, it verified whether military expenditure is an economically non-contributive activity using ARDL bounds testing approach to co-integration. Results showed that military spending has negative and significant effect on output in the short-run but positive and significant effect in the long-run. Labour and capital have positive and significant effects both in the long-run and short-run. In addition, labour has the highest coefficient (3.0709) in the long-run. The study concludes that government should reduce its expenditure on defense and concentrate more on human capital development, since military spending contributes nothing to output in the short-run.
Keywords: H56; C32; O40; E31; 330; military spending; co-Integration ARDL; economic growth; Inflation